2014
DOI: 10.1038/ajg.2014.28
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Previous Night Call and Sleep Deprivation on Screening Colonoscopy Quality

Abstract: (1) Despite longer withdrawal times, being on call the night prior and performing an emergent procedure lead to a significant 24% decrease in the adenoma detection rates. (2) It is imperative for screening physicians to be aware of the influence of sleep deprivation on procedural outcomes and to consider altering their practice accordingly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 36 publications
0
8
0
1
Order By: Relevance
“…Recently, a study from the English Bowel Cancer Screening Programme (11) speculated endoscopist fatigue as a factor for decreased ADR because it was found that the earlier the colonoscopy in the procedural list, the higher the ADR. Operator fatigue has also been shown to affect AD during screening colonoscopy when performed by endoscopists who performed emergent on-call procedures the night before performing screening colonoscopies when compared with those who were not on call (30% versus 39%, respectively; P=0.043) (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a study from the English Bowel Cancer Screening Programme (11) speculated endoscopist fatigue as a factor for decreased ADR because it was found that the earlier the colonoscopy in the procedural list, the higher the ADR. Operator fatigue has also been shown to affect AD during screening colonoscopy when performed by endoscopists who performed emergent on-call procedures the night before performing screening colonoscopies when compared with those who were not on call (30% versus 39%, respectively; P=0.043) (13).…”
Section: Discussionmentioning
confidence: 99%
“…effectiveness of colonoscopy. Some studies suggest that operator fatigue, either as a function of the time of day (10), queue position (11,12) or performing emergency procedures the night before the colonoscopy (13), may affect quality (14) and the detection of polyps (15) and adenomas (16), while others have not found this association (17,18). These metrics, as well as others, have been stressed in the clinical practice guideline by Tinmouth et al (19) for colonoscopy quality assurance in Ontario.…”
mentioning
confidence: 99%
“…A retrospective analysis by Benson et al [42], demonstrated significantly lower adenoma detection rates in procedures performed by gastroenterologists who had been "called in" (we assume on-call from home) for emergency procedures the previous night, compared to when procedures were performed by gastroenterologists who had not been on-call the previous night. Another study, not specifically investigating on-call work, found that there were more complications in cases the day after a night with a sleep opportunity of six hours or less compared to when doctors had a sleep opportunity of more than six hours [43].…”
mentioning
confidence: 99%
“…Similarly, although factors such as participation in an endoscopic quality improvement project, night call and sleep deprivation, withdrawal time, and breaks in training have previously been determined to affect colonoscopy performance, these specific variables were not investigated in this study. [22][23][24][25] Finally, although this study focuses on technical competency in colonoscopy, recently published guidelines for monitoring of fellow competency focus not only on technical, but also cognitive, and integrative competencies such as that proposed by Walsh et al 16 We too, appreciate that the competency of a gastroenterologist to perform high-quality colonoscopy independently is not solely a function of technical skill, but also those stated in recently updated societal guidelines. 13,16,18 To this point, it should be noted that the quality of preprocedural prep instructions and documentation of an appropriate repeat colonoscopy interval postprocedure, 2 quality metrics not included in this study, are also important metrics for independent GI practice.…”
Section: Discussionmentioning
confidence: 95%